ULTRASOUND AND MAGNETIC RESONANCE ENTEROGRAPHY IN DIAGNOSIS OF CROHN’S DISEASE IN CHILDREN - Cvejić, Sofija; Filipović, Sara; Pavićević, Polina; Vukadinović, Vojkan (Medicinski podmladak, 2018)
Abstract Introduction Crohn's disease is a chronic inflammatory bowel disease, which is characterized by remitting and relapsing episodes, and commonly affects young adults. MR enterography (MRE) and US are taking the leading role in diagnostics, initial estimation of Crohn’s disease and monitoring of activity, detection and evaluation of complications. Aim To examine SE, SP, PPV, NPV of US and MRE in diagnosis of Crohn’s disease. Also, to examine overall diagnostic value of MRE comparing the morphological and functional parameters with the endoscopical findings. Material and methods 40  patients were observed from the end of year 2009 to the end of 2016. Diagnosed patients with clinical and laboratory findings were sent for US and MRE examination. US evaluated wall thickness, fibrofatty proliferation and enlargement of mesenteric lymph nodes. Besides this, MRE also evaluated bowel wall enhancement and layered enhancement pattern. Results Overall diagnostic value of morphological and functional parameters on  the MRE has a SE of 58.3% and SP of 100% if we want to confirm the diagnosis, and SE 87.5%  and SP of 80%  if  we want  to  exclude the  diagnosis. There was statistically significant correlation between the increased wall thickness and the accumulation of fat in the mesentery on MRE, and the gold standard. Correlation between results on US and MRE shows statistical significance in ileum, terminal ileum, Bauchini valve and cecum, ascendant colon. It showed high specificity (SP) for both diagnostic procedures in almost all segments (maximum value 94,7%). Sensitivity (SE) varied from 0 to 83,3% in different bowel segments. Conclusion Our study showed that it is reliable to use MRE and US to exclude those who don’t have Crohn’s disease. Also, combination of morphological and functional parameters on MRE could be used in confirming and monitoring Crohn’s disease. Key words: Crohn’s disease, children, magnetic resonance enterography, ultrasound